2021
DOI: 10.1038/s41598-021-99014-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the SARS-CoV-2 genomes in Egypt in first and second waves of infection

Abstract: At Wuhan, in December 2019, the SRAS-CoV-2 outbreak was detected and it has been the pandemic worldwide. This study aims to investigate the mutations in sequence of the SARS-CoV-2 genome and characterize the mutation patterns in Egyptian COVID-19 patients during different waves of infection. The samples were collected from 250 COVID-19 patients and the whole genome sequencing was conducted using Next Generation Sequencing. The viral sequence analysis showed 1115 different genome from all Egyptian samples in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…Our study shows a higher number of missense mutations than synonymous mutations, and half of them were located in the ORF1ab gene followed by the S gene (49 missense mutations). A similar observation was reported in studies conducted in Colombia and Egypt ( Bermúdez-Forero et al, 2021 ;Sahin et al, 2021 ;Zekri et al, 2021 ;Maitra et al, 2020 ). Interestingly, the L4715L mutation found in 60 SARS-CoV-2 sequences from this study corroborates with previous findings reporting the P4715L mutation as a potential antiviral drug target ( Pachetti et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our study shows a higher number of missense mutations than synonymous mutations, and half of them were located in the ORF1ab gene followed by the S gene (49 missense mutations). A similar observation was reported in studies conducted in Colombia and Egypt ( Bermúdez-Forero et al, 2021 ;Sahin et al, 2021 ;Zekri et al, 2021 ;Maitra et al, 2020 ). Interestingly, the L4715L mutation found in 60 SARS-CoV-2 sequences from this study corroborates with previous findings reporting the P4715L mutation as a potential antiviral drug target ( Pachetti et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…S477N and P681H were found to confer resistance to antibody therapy 29 , 33 , whereas contradictory reports were reported for IHV68I 34 , 35 . A study on 176 viral genome sequences from Egypt showed mutation patterns similar to those found in our data 36 .…”
Section: Discussionsupporting
confidence: 87%
“…Towards the end of 2020, more distinct viral lineages started to appear. The most important of which that impacted the African continent are: B.1.525 (n=797), B.1.1.318 (n=398) ( 35 ), B.1.1.418 (n=395), A.23.1 (n=358) (( 15, 29, 31, 33 )), C.1 (n=446) ( 29 ), C.1.2 (n=300) ( 31 ), C.36 (n=305) ( 30, 36 ), B.1.1.54 (n=287) (( 15, 29, 31, 33 )), B.1.416 (n=272), B.1.177 (n=203), B.1.620 (n=138), and B.1.160 (n=61), ( 32 ) ( Supp Fig S3A,B ). From our discrete state phylogeographic inference we infer at least 2,151 (95% CI: 2,132 - 2,170) viral introductions of non-VOC lineages into African countries over the course of the pandemic.…”
Section: Resultsmentioning
confidence: 99%